Inquiry Learning-based Natural and Social Sciences Student Worksheet to Grow Elementary School Students’ Critical Thinking Skills - Ridwan Jusuf; Asri S Tamalene; Ratna Sari Dewi (Jurnal Ilmiah Sekolah Dasar, 2024)
The student worksheets of Natural and Social Sciences developed by teachers are not yet based on learning models that can encourage students to solve problems, resulting in weak and underdeveloped critical thinking skills of students, student activities tend to be more note-taking, and learning activities tend to be dominated by memorization to master knowledge. This study aims to develop a Student Worksheet of Natural and Social Sciences based on inquiry learning to foster critical thinking skills in elementary school students. This research method uses the 4-D model development research method. Data collection techniques use validation sheets, student and teacher response questionnaires, and test questions. Validation sheets are used to obtain data on the validity of Student Worksheets, questionnaires are used to record teacher and student responses to the practicality of Student Worksheets, and Tests are used to measure students' critical thinking skills. The data analysis technique used is descriptive data analysis techniques. The results of the validation of Student Worksheets show that the average percentage of material and media expert validators is in the very valid category. At the same time, the responses of teachers and students are in the convenient category. The worksheets for students of natural and social sciences based on inquiry learning that was developed have also proven to be effective in developing critical thinking skills in elementary school students, as evidenced by the significant difference in the average value of students' critical thinking skills between the experimental class and the control class.